2013
DOI: 10.1007/s13595-013-0350-4
|View full text |Cite
|
Sign up to set email alerts
|

Using density management diagrams to assess crown fire potential in Pinus pinaster Ait. stands

Abstract: International audienceContextDensity management diagrams (DMDs) are useful for designing, displaying and evaluating alternative density management regimes for a given stand-level management objective. The inclusion of variables related to crown fire potential within DMDs has not previously been considered.AimsThe aim of this study was to include isolines of variables related to crown fire initiation and spread in DMDs to enable identification of stand structures associated with different types of wildfire.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 30 publications
5
10
0
Order By: Relevance
“…Basal area is the stand characteristic that has shown to have a clear effect on the occurrence of wildfires on the Iberian Peninsula. These results are consistent with those reported by Fernández-Alonso et al (2013), who estimates the canopy fuel characteristics in relation to crown fire potential in pine stands in north-western Spain and found that stand basal area was the most important variable for estimating canopy fuel loads and canopy bulk density. Also, González-Ferreiro et al (2017) found that stand basal area was an important variable to estimate the vertical profiles of canopy fuels in P. radiata stands in north-western Spain.…”
Section: Occurrence Of Wildfires In Iberian Peninsula Based On Harmonsupporting
confidence: 92%
See 2 more Smart Citations
“…Basal area is the stand characteristic that has shown to have a clear effect on the occurrence of wildfires on the Iberian Peninsula. These results are consistent with those reported by Fernández-Alonso et al (2013), who estimates the canopy fuel characteristics in relation to crown fire potential in pine stands in north-western Spain and found that stand basal area was the most important variable for estimating canopy fuel loads and canopy bulk density. Also, González-Ferreiro et al (2017) found that stand basal area was an important variable to estimate the vertical profiles of canopy fuels in P. radiata stands in north-western Spain.…”
Section: Occurrence Of Wildfires In Iberian Peninsula Based On Harmonsupporting
confidence: 92%
“…Fires occur because of a combination of predisposing weather, fuel conditions and ignition agents, resulting this last one from human activities or natural events (Lavorel et al 2007). The behaviour of a wildfire can be predicted by the stand forest characteristics collected on NFIs and have been explored by several authors (Lentile et al 2006;Fernandes 2009;Alvarez et al 2012;Fernández-Alonso et al 2013).…”
Section: The Role Of Nfi On Fire Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same direction is the work developed by Castedo et al (2012), which shows that, in general and also in particular for maritime pine in Galicia, the higher the tree density, the lower the above ground fuel load (due to the shadowing effect of the trees on the understory), and therefore the fuel model would lead to wildfires of a lower magnitude. With respect to the height of the forest stand, in general, the higher the trees, the lower the probability of a fire reaching the crowns and propagating through them, increasing the magnitude of the wildfire, as Gómez-Vázquez et al (2014) found for maritime pine.…”
Section: Classification Of the Forest Stands Regarding The Magnitude mentioning
confidence: 72%
“…Adaptive management actions, such as the modification of the structure and quantity of aerial and surface fuels to manage fire hazard (e.g., prescribed fire) or the use of silvicultural models more oriented to control the proliferation of shrubs, are therefore essential. It is often advocated that high densities should be maintained as a control measure over the understory vegetation (Gomes & Alves 1968, Rodríguez-Soalleiro et al 1997, given that P. pinaster presents a sparse canopy that facilitates the passage of light to the ground, thereby promoting the development of an abundant undergrowth (Rodríguez-Soalleiro et al 1997, Rigolot & Fernandes 2005, Gómez-Vázquez et al 2014. In fact, the impact of density on the occurrence of understory happens due to the interception of irradiance by the canopy and can be assessed by the metric Leaf Area Index (LAI) of the canopy.…”
Section: Introductionmentioning
confidence: 99%